A participação dos conselhos profissionais na avaliação da educação superior no Brasil: uma análise do Conselho Regional de Administração do Paraná nos anos de 2011 e 2016 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The main objective of this thesis is to understand and evaluate the implications of the participation of the Regional Board of Directors of Paraná in the evaluation processes of higher education through the e-MEC system in 2011 and 2016. From the contextualization of the expansion and evaluation of higher education from 1990, where the evaluative culture emerges through the development of new state instruments, the proposal intends to evaluate higher education through the National System of Higher Education Assessment (Sinaes) in the way in which the collaboration of regulated professions in the evaluation process takes place, their limits and possibilities. For the foundation and theoretical analysis, two complementary theories were highlighted, being the Sociology of Professions and the Theory of communicative action (TAC), with the perspective of intertwining such theories with the discussion of the expansion of understanding and participation of society in evaluations. The methodological orientation used was the case study. The thesis demonstrates how CRA-PR’s participation was constituted in the processes of regulation of Sinaes from Decree No.5773/06 (BRASIL, 2006), and through analysis and evaluation of the Reports and Opinions issued by CRA-PR to the e-MEC system. It is pointed out that the participation of professional councils in the evaluation of higher education presupposes encouragement and consolidation on the democratic participation of civil society through professional councils. There is also a the reflection on the attributions of the Councils regarding professional training and insertion in the world of work, their approaches and their limits and finally the advance on the expected quality in higher education, constituting development in the evaluation methodology. The potentialities and inconsistencies presented are inherent to innovative models, which can therefore be improved to achieve quality as a desired result.
Keywords: Avaliação; Educação superior; Participação; Formação profissional; Assessment.; Higher education; Participation; Vocational training; CNPQ::CIENCIAS SOCIAIS APLICADAS